The Culture of Angkut Pari in Javanese Society Form of Agricultural Culture - Sawitri, Sawitri; Pujiyana, Pujiyana (LifeSciFi, 2024)
Culture will adapt to where society exists and always adapts to people’s lives. Activities carried out by farming communities in Java include the culture of transporting rays. The farming community’s habit at harvest time is to bring the harvest from the fields to the barn to be stored as food reserves. In Javanese society, the culture of carrying stingrays is a habit that is carried out continuously and has become a tradition. Data was obtained by document study, interviews, and using online media, online magazines, and social media. Community behavior passed down from generation to generation at harvest time makes this habit a routine tradition. Farmers make ngangkut pari a ritual carried out to pay respects to the goddess Sri, the god of rice. Earth’s products should be protected and cared for for human survival. Farmers’ livelihoods provide needs in the agricultural sector, with more and more successful farmers bringing prosperity to society. Preserving human culture must ensure that it continues to exist and is sustainable for the survival of Javanese society. A form of agricultural culture that should remain sustainable.